APLIKASI RAGAM HIAS BATIK CIMAHI PADA KARYA KERAMIK BAS RELIEF TILES - Nadiya Alsajira, - (2022)
In everyday life we can see various kinds of works of art that have been created by humans, but not all humans know the origins of making these works of art, for example the motifs of batik Cimahi which is rarely known by the public and also ceramic relief art which is rarely known how to make it. So it is necessary for someone to introducing batik Cimahi and ceramic relief art so that it can be known by the wider community, as someone who is steeped in the field of fine arts, the author is concerned about the lack of public knowledge about the forms of Cimahi batik motifs and ceramic relief art. Therefore, this led to the idea of applying Cimahi batik motifs to ceramic bas relief tiles. The purpose of this creation is to explain the process and application of Cimahi batik motifs to ceramic works of bas relief tiles and to be able to visualize concepts and describe the visualization of works from the theory of elements and principles of art. The results of this creation work through exploration of works carried out two to three times so as to produce three ceramic relief works with Cimahi batik motifs as wall decorations, The first motif that many people choose is Ciawitali, the second is Cirendeu, and the third is Kujang Cimahi. The technique used is a mixture of ceramic techniques and techniques for making bas relief tiles. It is hoped that the results of this creation can introduce Cimahi batik motifs and develop ceramic relief art to be more creative, innovative, and provide inspiration and learning in ceramic work.